2021
DOI: 10.1208/s12249-021-01931-0
|View full text |Cite
|
Sign up to set email alerts
|

Preformulation Characterization of Griffithsin, a Biopharmaceutical Candidate for HIV Prevention

Abstract: Griffithsin (GRFT) has shown potent anti-HIV activity, and it is being developed as a drug candidate for HIV prevention. Successful implementation requires thorough understanding of its preformulation characterization. In this work, preformulation assessments were conducted to characterize GRFT and identify its degradation pathways under selected conditions of temperature, light, pH, shear, ionic strength, and oxidation. Compatibility with vaginal fluid simulant, vaginal enzymes, Lactobacillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…coli at a scale of tons . In addition, rGRFT is reported to be stable at room temperature in PBS for 2 years without formation of aggregation and degradation byproducts . Considering the board activity of rGRFT on different coronaviruses, the evolutionary cost of glycan loss on SARS-CoV-2, the available high-yield recombinant production strategies for rGRFT, and the good stability of rGRFT at room temperature, rGRFT may provide a possible solution for the emerging variants.…”
Section: Discussionmentioning
confidence: 99%
“…coli at a scale of tons . In addition, rGRFT is reported to be stable at room temperature in PBS for 2 years without formation of aggregation and degradation byproducts . Considering the board activity of rGRFT on different coronaviruses, the evolutionary cost of glycan loss on SARS-CoV-2, the available high-yield recombinant production strategies for rGRFT, and the good stability of rGRFT at room temperature, rGRFT may provide a possible solution for the emerging variants.…”
Section: Discussionmentioning
confidence: 99%
“…48 In addition, rGRFT is reported to be stable at room temperature in PBS for 2 years without formation of aggregation and degradation byproducts. 49 Considering the board activity of rGRFT on different coronaviruses, evolutionary cost of glycan loss on SARS-CoV-2, available high-yield recombinant production strategies for rGRFT and good stability of rGRFT at room temperature, rGRFT may provide a possible solution for emerging variants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GRFT synergizes with the HIV-1 drugs tenofovir, maraviroc, and enfuvirtide, which could be used for microbicide development [ 162 ]. Kramzer et al performed in vitro characterization of a preformulation of this compound and found physical, chemical, and biological stability profiles under stress conditions, except oxidative stress [ 163 ]. GRFT, being a lectin, is prone to oxidation; to overcome this property, an oxidation-resistant form of GRFT (Q-GRFT) has been developed and evaluated in rhesus macaque rectal tissue samples showing a nontoxic effect [ 164 ].…”
Section: Proteinsmentioning
confidence: 99%